Improvement of Motivation and Ability to Solve Problem in Mathematical Learning Using Problem Solving Method in Class VI Sdn 07 Koto Alam Kecamatan Palembayan - Halomoan Halomoan; Hendra Syarifuddin; Dadan Suryana (Postgraduate School, Universitas Negeri Padang, 2019)
This study aims to improve problem solving skills by using problem solving methods of class VI students of Koto Alam 07 State Elementary School, Palembayan District, Agam Regency. The type of research used is Classroom Action Research. The population in this study were students of class VI of SD Negeri 07 Koto Alam, Palembayan Subdistrict, Agam Regency, who were enrolled in the first semester of the 2017/2018 school year. Class VI students number 34 people, consisting of 12 men and 22 women. This study focused on the average score of problem solving abilities of students in cycles I and II. The following data presents the results of the test: The problem solving ability of students in cycle 1 is the percentage of the classic average obtained from the test of 56%. Looking at the circumstances that occur as well as the classical average, the average percentage of students' problem solving abilities in cycle 1 is only 61%, so this is far below the indicator of success set at 75%. In cycle II the problem solving ability of students from the test with an average score of 78%.